2020
DOI: 10.1002/emp2.12123
|View full text |Cite
|
Sign up to set email alerts
|

What influences safety in paramedicine? Understanding the impact of stress and fatigue on safety outcomes

Abstract: Objective The purpose of this study was to build on extant research linking fatigue to safety outcomes in paramedicine by assessing the influence of a multiplicity of workplace stressors, including chronic and critical incident stresses on safety outcomes. Methods A cross‐sectional survey was deployed to 10 paramedic services in Ontario. Validated survey instruments measured operational and organizational chronic stress, critical incident stress, post‐traumatic stress symptomatology (PTSS), fatigue, safety out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Finally, we observed an encouraging and considerable increase in literature exploring health and wellbeing in paramedicine over the past decade. We identified a total of 60 reports exploring paramedic physical health [36,37], safety [38,39], mental health [40,41], violence against paramedics [42], mental health supports and interventions [43], and family and social supports [44]. However, we observed a continued lack of understanding related to spirituality, holistic self-care, empathy, compassion, and the impacts of and influences on paramedicine culture.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we observed an encouraging and considerable increase in literature exploring health and wellbeing in paramedicine over the past decade. We identified a total of 60 reports exploring paramedic physical health [36,37], safety [38,39], mental health [40,41], violence against paramedics [42], mental health supports and interventions [43], and family and social supports [44]. However, we observed a continued lack of understanding related to spirituality, holistic self-care, empathy, compassion, and the impacts of and influences on paramedicine culture.…”
Section: Discussionmentioning
confidence: 99%
“…Paramedics' injuries showed a significant association with fatigue and critical stress. Considering that medication errors were also significantly associated with fatigue [43] it should be noted that the safety of patients depends on the psychophysical condition of medical personnel, in particular with the increase in stress factors and fatigue [43].…”
Section: Psychophysical Condition Of Health Care Workers Vs the Safet...mentioning
confidence: 99%
“…The safety of the rescue team, the patient and other road users depends on the speed of the driver's reaction, which can be reduced by prolonged stress. Based on author's own observations, in recent years an increasing number of accidents involving ambulances and rescue motorcycles can be noticed [43]. Lifshitz et al [45] indicated that mistakes occurred in up to 12.76% of medication administrations in prehospital care.…”
Section: Psychophysical Condition Of Health Care Workers Vs the Safet...mentioning
confidence: 99%
“…Related research has also suggested that exposure to potentially psychologically traumatic events [10][11][12][13][14][15][16]; symptoms consistent with chronic pain, [17] clinical insomnia [18] and alcohol use disorder [9]; suicidal ideation, planning, and attempts [19]; and a history of adverse childhood experiences [20] are prevalent among paramedics, again varying across demographic categories, including gender. The downstream consequences are potentially significant, and can include lost time from work [21], family hardship [22], reduced quality of life [23][24][25][26], and suicidality [7,27], all of which can contribute to burnout [6,28], workplace incivility [29,30], attrition [31] and potentially compromise patient care [32]. As a result, the situation has been characterized in research and policy as a 'crisis in Canada' [33,34].…”
Section: Introductionmentioning
confidence: 99%